Pemetaan Kluster Perumahan di Kecamatan Biringkanaya dan Tamalanrea Kota Makassar dengan Quantum GIS - Ridwan, Vita Fajriani; Hasanuddin, Haeril Adi (Politeknik Negeri Ujung Pandang, 2018)
Biringkanaya and Tamalanrea sub-districts areMakassar's eastern suburbs that experience urban sprawl.Regional sprawl (urban sprawl) which occurs one of them isindicated due to uncontrolled housing cluster growth. Thephenomenon of urban sprawl has an impact on city morphology,transportation systems, environment and energy. This study aimsto analyze the distribution pattern and density level of housingclusters in Biringkanaya and Tamalanrea sub-districts throughmapping housing clusters in the region. This research method iscarried out by survey for primary data collection in the form ofhousing cluster and area using Garmin 76 CSX which will becombined with Quickbird imagery maps using Quantum GIS,then digitizing buildings from GPS data overlay and image maps.The results of this study are clear spatial data in the form of adigital map based on geographic information about the positionand density of residential clusters in Biringkaya Subdistrict andTamalanrea District, Makassar City. From the results of thisanalysis found housing cluster patterns in these two sub-districtsscattered following the Independence Pioneering arterial pathwith a spawling pattern, besides that it also uses a dominopattern and fills between one housing and another. AlsoBiringkanaya Subdistrict is the most populous sub-district of itshousing cluster compared to Kecamatan Tamalanrea.